(untitled) (Journal of Educational Sciences, 2023)
The article describes the program of the trigonometry section in the school mathematics course and the application of trigonometry in life. The introduction defines trigonometric equations and mentions the types of solutions to the equation. The examples show methods for solving trigonometric equations. The ways of solving simple trigonometric equations and the possibilities of their independent solution are illustrated. Separately, methods for solving equations were noted, which are actually little used in the school mathematics course. According to the results of the study, about ten types of methods for solving trigonometric equations were identified. In order to reveal the essence of the methods of solving trigonometric equations, the problems for each method are considered and the ways of deducing these problems are shown. In addition, this article discussed the difficulties faced by students in solving trigonometric equations, and the methods proposed by A. G. Mordkovich in solving these problems. In the final part, the results of the methodological experience of teachers are summarized, when students practiced solving a series of problems on the topic “Methods for solving trigonometric equations” and teachers identified abilities that can be developed in students to solve the equation. In the future, it is planned to publish a specific methodological manual on the topic “Trigonometric equations and inequalities”. Key words: trigonometric equation, methodology, equation solution, methods.